Kolonizacja stawów hydr – narracje w serii Heroes of Might and Magic - Czyżak , Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This article is an analysis of narratives in a series of video games called Heroes of Might and Magic. Author discusses issue of colonial/imperial thinking connected with strategy genre, evolution of fantasy tropes and developement of plot structure. On this basis he tries to outline the limitations of storytelling which result from series formula.